超音波工具、および工具を製造するための方法 (2023)
超音波器具において用いるための超音波切削工具であって、この工具は、管状ブランクの一部分を扁平にすることによってブランクから製造されるブレード（１０）であり、このブレード（１０）は、切削に用いられるように設計された扁平部（１１）と、管状部（１３）と、扁平部（１１）を管状部（１３）に接合する遷移部（１２）とを備え、管状部（１３）は、ブレード（１０）を超音波発生器に取り付けるための取付部（１４）に接合されるか、またはこの取付部（１４）を含み、冷却液を遠位端に導くかまたは手工具における粒子を吸引するための導管である。 An ultrasonic cutting tool for use in an ultrasonic instrument, the tool being a blade manufactured from a tubular blank by flattening a section of the blank. The blade includes a flat section designed to be used for cutting, a tubular section, and a transition section joining the flat section to the tubular section. The tubular section is joined to or includes an attachment section for attaching the blade to an ultrasonic generator and serving as a conduit to bring a cooling fluid to the distal end or to suck particles into the hand tool.